2018
DOI: 10.1371/journal.pone.0203826
|View full text |Cite
|
Sign up to set email alerts
|

Turning off the empathy switch: Lower empathic concern for the victim leads to utilitarian choices of action

Abstract: Empathy enables people to vicariously experience the other’s pain. At the same time, the focus of empathy can be narrow and reserved for a limited number of people. In sacrificial dilemmas, non-empathic people are more likely to sacrifice one person for greater good. However, no study has investigated the role of diminished empathic concern for the victim in utilitarian choices of action. In two studies, we investigated how empathy actually experienced in sacrificial dilemmas affects a decision to perform a ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 52 publications
1
8
1
3
Order By: Relevance
“…EF plays a role in this process; at the least, some of its subcomponents may be a construct of empathetic behavior. Takamatsu () also found that other‐oriented empathy, rather than self‐oriented empathy, might predict our later prosocial behavior, which is closely related to EF (Valiente et al, ). Executive function would thus act as a switch to modulate our empathy for others’ emotions, and high EF would be a prerequisite for high empathy (Decety & Meyer, ; Heyes, ).…”
Section: Empathymentioning
confidence: 75%
“…EF plays a role in this process; at the least, some of its subcomponents may be a construct of empathetic behavior. Takamatsu () also found that other‐oriented empathy, rather than self‐oriented empathy, might predict our later prosocial behavior, which is closely related to EF (Valiente et al, ). Executive function would thus act as a switch to modulate our empathy for others’ emotions, and high EF would be a prerequisite for high empathy (Decety & Meyer, ; Heyes, ).…”
Section: Empathymentioning
confidence: 75%
“…The former describes the ability to feel what others feel, and the latter refers to the capacity to comprehend others' perspectives and put oneself in someone's shoes. Several authors found that (1) a lack of affective empathy characterized psychopathy or antisocial traits, and (2) that this affective empathy depletion predicted group-oriented choices significantly in Trolley Problems Gleichgerrcht & Young, 2013;Decety & Cowell, 2014;Patil & Silani, 2014;Takamatsu, 2018;Burghart & Mier, 2021).…”
Section: Greene and Collaborators Popularized These Problems In 2001 With Their Publication Inmentioning
confidence: 99%
“…Through them, we aim to go closer to the foundation of relationships in the more-than-human world. In terms of ethical consideration, affective and embodied forms of empathy are also argued to play a critical role as they help to understand the difference of others, motivate helping behaviours, and make harming others aversive (Aaltola, 2018;Patil & Silani, 2014;Takamatsu, 2018).…”
Section: Aim Of Ecosocialization -Ethics Of the More-than-humanmentioning
confidence: 99%